1993
DOI: 10.1136/pgmj.69.809.197
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a short course of three lipid lowering drugs on fat oxidation during exercise in healthy volunteers

Abstract: UK Summary:We examined the impact ofthree lipid lowering drugs on fat oxidation during a 120 minute treadmill walk, at an exercise intensity of 50% maximal oxygen uptake (Vo2 max). Subjects (N = 24) were healthy male volunteers with normal serum chemistry, assigned to three groups (n = 8). Group A received simvastatin 20 mg twice daily, Group B received gemfibrozil 600 mg twice daily, Group C received acipimox 600 mg twice daily. Each subject performed two 120 minute walks, once with drug, and once with placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
3
23
1
Order By: Relevance
“…The decrease in total body fat oxidation associated with lipid-lowering drugs observed in the statin-tolerant group in the present study and previous studies (Head et al 1993;Phillips et al 2002Phillips et al , 2004 may be due to the impairment in the availability of substrate, substrate transport or mitochondrial dysfunction. Patients with mutations in the CPT2 gene demonstrate reduced fat oxidation due to transport limitations (Vladutiu et al 2002), as do patients with rhabdomyolysis (Lofberg et al 1998); however, CPT2 gene deficiencies were not observed in the patients in the present study, suggesting substrate availability or mitochondrial factors as the mechanism of low fat oxidation in the tolerant group.…”
Section: Total Body Fat Oxidationcontrasting
confidence: 51%
See 2 more Smart Citations
“…The decrease in total body fat oxidation associated with lipid-lowering drugs observed in the statin-tolerant group in the present study and previous studies (Head et al 1993;Phillips et al 2002Phillips et al , 2004 may be due to the impairment in the availability of substrate, substrate transport or mitochondrial dysfunction. Patients with mutations in the CPT2 gene demonstrate reduced fat oxidation due to transport limitations (Vladutiu et al 2002), as do patients with rhabdomyolysis (Lofberg et al 1998); however, CPT2 gene deficiencies were not observed in the patients in the present study, suggesting substrate availability or mitochondrial factors as the mechanism of low fat oxidation in the tolerant group.…”
Section: Total Body Fat Oxidationcontrasting
confidence: 51%
“…Their fat oxidation was normal during this study while they were symptom free. A previous study (Head et al 1993) demonstrated that simvastatin had no impact on fat oxidation or plasma concentration of free fatty acids and glycerol or glucose in tolerant subjects, while gemfibrozil decreased fat oxidation and lowered plasma concentrations of FFA and glycerol (32%). Acipimox reduced fat oxidation and lowered plasma concentrations of FFA and glycerol, thus reducing fat availability for exercise metabolism (Head et al 1993).…”
Section: Total Body Fat Oxidationmentioning
confidence: 96%
See 1 more Smart Citation
“…14 Interestingly, in the latter study, the resting respiratory exchange ratio (RER; an index of fat and carbohydrate metabolism) increased with statin therapy in both asymptomatic and symptomatic statin users, consistent with other reports suggesting that statins decrease or impair fat oxidation. [15][16][17] An altered RER attributable to statins could alter exercise metabolism and diminish aerobic exercise performance.…”
mentioning
confidence: 99%
“…Hormone-sensitive lipase (HSL), an intracellular enzyme in adipose tissue, and lipoprotein lipase (LPL), an enzyme which hydrolyzes the triglyceride core of circulating chylomicrons, both liberate free fatty acids (FFA) for use by exercising muscle. Any drugs acting at these sites, could potentially alter FFA availability, which may result in increasing dependence on muscle glycogen stores and possible earlier fatigue [5]. An early study examining muscle biopsies of quadriceps femoris has documented glycogen depletion in healthy males while cycling in the presence of the lipid-lowering drug acipimox, also known as nicotinic acid [6].…”
Section: Introductionmentioning
confidence: 99%